2012
DOI: 10.1111/j.1365-2958.2012.07985.x
|View full text |Cite
|
Sign up to set email alerts
|

The mammalian cell entry (Mce) protein of pathogenic Leptospira species is responsible for RGD motif‐dependent infection of cells and animals

Abstract: SummaryMammalian cell entry proteins (Mces) contribute to Mycobacterium tuberculosis virulence. A mce homologue has been identified in the Leptospira interrogans genome, but its function was unknown. We showed that the mce gene is expressed only by pathogenic Leptospira strains tested. Leptospiral mce mRNA and Mce protein levels increased during infection of macrophages. The ability to infect macrophages was significantly lower in a strain with the mce gene deleted (mce

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
87
1
7

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 86 publications
(95 citation statements)
references
References 73 publications
0
87
1
7
Order By: Relevance
“…The lack of involvement in disease pathogenesis by the majority of exoproteins is in agreement with the findings of previous studies on L. interrogans virulence genes which have demonstrated that the majority of genes are dispensable for virulence (27,68). Moreover, with the exception of a catalase gene (katE) (34) and a collagenase gene (24), the genes that have been demonstrated to be essential for virulence, such as HtpG (63), Loa22 (69), and those involved in motility (11,12), LPS biosynthesis (13), heme metabolism (70), and adhesion (71,72), have orthologues in the nonpathogenic species L. biflexa. In combination with the finding that the majority of L. interrogans exoproteins have orthologues in L. biflexa, this evidence further supports the theory that L. interrogans evolved from L. biflexa.…”
Section: Discussionmentioning
confidence: 69%
“…The lack of involvement in disease pathogenesis by the majority of exoproteins is in agreement with the findings of previous studies on L. interrogans virulence genes which have demonstrated that the majority of genes are dispensable for virulence (27,68). Moreover, with the exception of a catalase gene (katE) (34) and a collagenase gene (24), the genes that have been demonstrated to be essential for virulence, such as HtpG (63), Loa22 (69), and those involved in motility (11,12), LPS biosynthesis (13), heme metabolism (70), and adhesion (71,72), have orthologues in the nonpathogenic species L. biflexa. In combination with the finding that the majority of L. interrogans exoproteins have orthologues in L. biflexa, this evidence further supports the theory that L. interrogans evolved from L. biflexa.…”
Section: Discussionmentioning
confidence: 69%
“…L. interrogans transposon mutants disrupted in katE were constructed to assess the viability of these mutants under conditions of oxidative stress and during in vivo infection. Complementation in L. interrogans is extremely difficult and has been documented only twice (49,67). We compensated for this lack of a genetic "knock-in" capability by constructing independent mutations in two different L. interrogans serovars (L. interrogans serovar Pomona mutant strain P3 and L. interrogans serovar Manilae mutant strain m69) and assessing if similar results were obtained with each of these mutants.…”
Section: Resultsmentioning
confidence: 99%
“…Mutagenesis and biochemical studies found that integrin receptors exhibited variable degrees of affinity to organisms with the analogs or mutants of the RGD motif, depending on the property of the integrin-binding protein (44). Individual residues within the RGD motif in surface proteins of many bacteria (such as Shigella, Leptospira, and Streptococcus species) played a dominant role in binding to integrin receptors (45)(46)(47). However, in the type IV secretion system (T4SS) protein CagL of Helicobacter pylori, all three residues in the RGD motif are important for integrin binding, as evidenced that the finding that replacement of each of these residues with alanine abolished the adhesion function (48).…”
Section: Discussionmentioning
confidence: 99%